2018
DOI: 10.1097/sla.0000000000002050
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Complications After Surgery for MEN1-related Nonfunctioning Pancreatic Neuroendocrine Tumors

Abstract: MEN1 NF-pNET surgery is associated with high rates of major short and long-term complications. Current findings should be taken into account in the shared decision-making process when MEN1 NF-pNET surgery is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 29 publications
2
51
0
4
Order By: Relevance
“…Merging the need for pancreaticoduodenal resections to achieve biochemical cure on the one hand and the scarcity of data regarding postoperative complications and long-term oncological outcomes after pancreaticoduodenal resections on the other, future studies should address these topics to come to meaningful advice. 28 In conclusion, life expectancy in patients with MEN1 having gastrinomas is reduced compared with other studies. OS was associated with initial FSG levels ≥20x ULN, a pNET ≥2.0 cm on conventional imaging, synchronous liver metastases, multiple concurrent NETs, and gastroduodenoscopy suspicious for gastric NET in patients with MEN1.…”
Section: Prognostic Factors For Osmentioning
confidence: 72%
See 1 more Smart Citation
“…Merging the need for pancreaticoduodenal resections to achieve biochemical cure on the one hand and the scarcity of data regarding postoperative complications and long-term oncological outcomes after pancreaticoduodenal resections on the other, future studies should address these topics to come to meaningful advice. 28 In conclusion, life expectancy in patients with MEN1 having gastrinomas is reduced compared with other studies. OS was associated with initial FSG levels ≥20x ULN, a pNET ≥2.0 cm on conventional imaging, synchronous liver metastases, multiple concurrent NETs, and gastroduodenoscopy suspicious for gastric NET in patients with MEN1.…”
Section: Prognostic Factors For Osmentioning
confidence: 72%
“…Especially, in the coexistence of hypergastrinemia and pNETs ≥2.0 cm, the optimal surgical strategy is hard to establish. Merging the need for pancreaticoduodenal resections to achieve biochemical cure on the one hand and the scarcity of data regarding postoperative complications and long‐term oncological outcomes after pancreaticoduodenal resections on the other, future studies should address these topics to come to meaningful advice …”
Section: Discussionmentioning
confidence: 99%
“…Despite the aggressive protocol, 2 patients died of metastatic pNETs (Hausman et al 2004, Gauger et al 2009). Nell and coworkers (Nell et al 2016) also reported 33% of major early complications and 23% of endocrine and/or exocrine insufficiency among 61 patients with MEN1 who underwent pancreatic surgery in a Dutch academic center. These patients were young (median 41 years old) and in good general health (ASA score I or II for 89% of the patients), further emphasizing the negative impact of complications in this population.…”
Section: Non-functional Pancreatic Netsmentioning
confidence: 93%
“…47 Collectively, these data highlight the risk of significant post-operative morbidity associated with pancreatic surgery in MEN1. 47 Collectively, these data highlight the risk of significant post-operative morbidity associated with pancreatic surgery in MEN1.…”
Section: What Are the Tre Atment Op Ti On S For Nonme Ta S Tati C Mmentioning
confidence: 95%